Desiccation stress and tolerance in green algae: consequences for ultrastructure, physiological and molecular mechanisms - Holzinger, Andreas; Karsten, Ulf (Frontiers in Plant Science, 2013)
Although most green algae typically occur in aquatic ecosystems, many species also live partly or permanently under aeroterrestrial conditions, where the cells are exposed to the atmosphere and hence regularly experience dehydration. The ability of algal cells to survive in an air-dried state is termed desiccation tolerance. The mechanisms involved in desiccation tolerance of green algae are still poorly understood, and hence the aim of this review is to summarize recent findings on the effects of desiccation and osmotic water loss. Starting from structural changes, physiological and biochemical consequences of desiccation will be addressed in different green-algal lineages. The available data clearly indicate a range of strategies, which are rather different in streptophycean and non-streptophycean green algae. For example, Trebouxiophyceae exhibit effective water loss-prevention mechanisms based on the biosynthesis and accumulation of particular organic osmolytes such as polyols, these compounds are so far not reported in representatives of the Streptophyta. In members of the Streptophyta such as Klebsormidium, the most striking observation is the appearance of cross-walls in desiccated samples, which are strongly undulating, suggesting a high degree of mechanical flexibility. This allows the cell to maintain turgor pressure for a prolonged period of time during the dehydration process. Physiological strategies in aeroterrestrial green algae generally include a rapid reduction of photosynthesis during desiccation, but also a rather quick recovery after rewetting, whereas aquatic species are sensitive to drying. The underlying mechanisms such as the affected molecular components of the photosynthetic machinery are poorly understood in green algae. Therefore, modern approaches based on transcriptomics, proteomics and/or metabolomics are urgently needed to better understand the molecular mechanisms involved in desiccation-stress physiology of these organisms.